GC-MS Profiling and Evaluation of Antioxidant and invitro Anticancer Properties of Alstonia venenata R.Br. Leaves and Root: Life Sciences-Botany - Aarthi, J.; Geetha, N. (International Journal of Life Science and Pharma Research, 2022)
The study aimed to evaluate the efficacy of methanolic extracts of Alstonia venenata leaves and root for in vitro antioxidants and anticancer properties. The exploration of natural products by scientists is a highlighted subject today. Plants synthesize various chemical compounds, which are called secondary metabolites. Antioxidants inhibit oxidation stress and act as protective agents for multiple diseases, including breast cancer. Reactive oxygen species (ROS) and reactive nitrogen species (RNS) have been related in the pathogenesis of many human diseases including cancer. Breast cancer is one of the most destructive types of cancer among women throughout the world.GC-MS analysis was conducted to profile the potential phytocompounds responsible for anticancer activity. Generally, developing new drugs starts with identifying bioactive compounds from natural resources through various analytical techniques.Leaf and root samples were subjected to cold extraction using methanol for plant extraction. Gas chromatography-mass spectrometry was used to identify the phytocompounds present in the extracts. DPPH, ABTS, FRAP, H2O2, NO·, ·HO, lipid peroxidation, metal chelating, O2 -and reducing power were determined. Furthermore, MTT assay was performed to assess potential anticancer activity using MCF-7 cell lines.GC-MS analyses of leaf and root methanolic extracts revealed the presence(Methyl-α–d-glucopyranoside,Quinic acid)two and(2-Methylinosine, Methotrexate, 3-O-Methyl-D-Glucose, 2-O-Methyl-D-Xylose, D-Mannoheptulose, Hydroxyurea, Methyl-α–d-Glucopyranoside seven anti-cancerous compounds, respectively. Root extracts than leaf extract showed more antioxidant activities. Higher concentrations of leaf and root methanolic extracts caused a great reduction in the viability of MCF-7 cell lines. Cytotoxicity was found to be relatively higher in root methanolic extract (91.53%) than leaf methanolic extract (71.17%). The present work provides the first evidence for the presence of various anticancer phytocompounds in leaf and root extracts of A.venenata.